PENERAPAN METODE ROLE PLAYING DALAM PEMBELAJARAN KISAH NABI UNTUK MENINGKATKAN PEMAHAMAN SISWA SMP SAFINATUSSALAMAH KECAMATAN DANAU PARIS KABUPATEN ACEH SINGKIL - Ema Nursanti Ema Nursanti; Desriadi Desriadi (lembaga Sepercenter, 2024)
This study aims to analyze the effectiveness of the role-playing method in improving students' understanding of the story of the prophet at Safinatussalamah Junior High School, Danau Paris District, Aceh Singkil Regency. The role-playing method allows students to actively participate in learning by playing the characters in the story of the prophet, so that they better understand the content of the story, the moral message, and the values contained in it. This study uses a quantitative approach with a Classroom Action Research design. Data were collected through observation, interviews, comprehension tests, and student satisfaction questionnaires on the learning method. The results showed that the role-playing method significantly improved students' understanding of the story of the prophet. Students became more active, motivated, and able to remember and apply the values taught in their daily lives. Thus, the role-playing method can be used as an effective learning alternative in Islamic religious education